Telehealth Use Among U.S. Adults With Type 2 Diabetes: Differences In Medication Fill Patterns And Care Processes - Terrence T Liu; John Thomas Menchaca; Alexander Chaitoff; Boomer Olsen; Julia E Szymczak; Jorie Butler; Kensaku Kawamoto; Renuka Tipirneni; Molly B Conroy (Health Affairs Scholar, 2026)
Abstract Introduction The expansion of telehealth following the COVID-19 pandemic has enhanced access to care, but questions remain about how well telehealth supports the delivery of comprehensive, guideline-concordant care for type 2 diabetes. Methods We conducted an observational cross-sectional study using nationally representative survey data from the 2021–2023 Medical Expenditures Panel Survey to make unadjusted descriptive comparisons between adults with any diabetes-related telehealth use and those receiving only in-person diabetes care. Results Of 4348 respondents who had at least one visit for type 2 diabetes from 2021 to 2023, 90.7% had only in-person visits, whereas 9.3% had ≥1 telehealth visits. Insulin prescriptions were more common among telehealth users compared to nonusers (47.5% [95% CI, 41.0% - 54.1%] vs 34.4% [95%CI, 32.1% - 36.7%]). Conclusion Overall, this study provides current national data on patterns of telehealth use among U.S. adults with type 2 diabetes. Differences in insulin prescription fill patterns may reflect greater clinical complexity and care needs among patients who use telehealth. These findings offer important context for policymakers and health systems as they evaluate the role of telehealth in managing chronic disease and consider how virtual care models can be implemented while maintaining high-quality diabetes care.